2021
DOI: 10.1111/vop.12955
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of clinical evaluation for anterior uveitis through spectral‐domain optical coherence tomography in dogs

Abstract: Objective: To evaluate the clinical application of spectral-domain optical coherence tomography (SD-OCT) for anterior uveitis in dogs. Animals and procedures:Client-owned dogs presenting with anterior uveitis and clinically healthy dogs were enrolled in this study. Included eyes were divided into 5 groups by flare grade and 3 groups by cell grade through slit-lamp biomicroscopy. Each eye was examined using SD-OCT following slit-lamp biomicroscopy. The ratio of aqueous signal intensity to air signal intensity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Embora seja uma ferramenta oftalmológica muito útil na visualização das estruturas oculares, a biomicroscopia com lâmpada de fenda pode ter algumas limitações em situações de opacidade severa das estruturas oculares (HEINRICH, 2014). Nesses casos, outros exames complementares, como a ultrassonografia ocular ou a tomografia de coerência óptica, podem ser utilizados para auxiliar no diagnóstico (JEONG et al, 2021).…”
Section: Diagnóstico Da Emc E Suas Alterações Oftálmicas Secundáriasunclassified
“…Embora seja uma ferramenta oftalmológica muito útil na visualização das estruturas oculares, a biomicroscopia com lâmpada de fenda pode ter algumas limitações em situações de opacidade severa das estruturas oculares (HEINRICH, 2014). Nesses casos, outros exames complementares, como a ultrassonografia ocular ou a tomografia de coerência óptica, podem ser utilizados para auxiliar no diagnóstico (JEONG et al, 2021).…”
Section: Diagnóstico Da Emc E Suas Alterações Oftálmicas Secundáriasunclassified
“…A report comparing AS-OCT with UBM showed that while UBM offered better visualization of the posterior margin, AS-OCT provided better resolution of the anterior margin of the tumor than UBM [ 13 ]. In veterinary medicine, an increasing number of reports on the use of OCT for evaluating the anterior segment including the cornea, anterior chamber, and iridocorneal angle in dogs have been published [ 15 , 16 , 17 , 18 ]. However, there are no clinical reports focusing on the use of AS-OCT for examining iris lesions in cats.…”
Section: Introductionmentioning
confidence: 99%